Determination of the impact of ICT on the performance of MSMEs in Florencia Caquetá (Revista cientifica In Vestigium Ire, 2021)
This study analyzes the relationship between Information and Communication Technologies (ICTs) with the performance of godos and services and trade companies in Florencia, Caquetá in Colombia For the development of the research, an evaluation instrument directed to the managers or owners of MSMEs was used. As a methodological design, a stratified sample with a quantitative approach study was considered. The statistical technique used is descriptive and regression; as results it was obtained that for the best performance of these companies, the integration or strengthening in the use of ICT’s, is focused on the management of the orders with the suppliers and the control of the management of the human resources as for control of hours per day.
Keywords: TIC; performance; management; control; economic development